Report of the twenty-eighth seáion on the committee on fisheries. Rome (Italy). 2-6 march 2009 - FAO, Rome (Italy) (Rome (Italy), 2009)
Sumario (En)
Keywords: PESCA; DESARROLLO PESQUERO; RECURSOS PESQUEROS; COMERCIO; PAISES EN DESARROLLO; ASISTENCIA TECNICA